2007
DOI: 10.1038/sj.npp.1301591
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Colivelin Treatment Ameliorates Memory Impairment Related to Alzheimer's Disease

Abstract: Humanin (HN) and its derivatives, such as Colivelin (CLN), suppress neuronal death induced by insults related to Alzheimer's disease (AD) by activating STAT3 in vitro. They also ameliorate functional memory impairment of mice induced by anticholinergic drugs or soluble toxic amyloid-b (Ab) in vivo when either is directly administered into the cerebral ventricle or intraperitoneally injected. However, the mechanism underlying the in vivo effect remains uncharacterized. In addition, from the standpoint of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 38 publications
1
50
0
1
Order By: Relevance
“…Insulin-like growth factor-binding protein-3 enhances HN rescue activity from A␤ toxicity, whereas HN inhibited insulin-like growth factor-binding protein-3-induced apoptosis in human glioblastoma-A172 (Ikonen et al, 2003). In addition, multiple groups have demonstrated that HN derivatives inhibited memory impairment of AD model animals (Mamiya and Ukai, 2001;Krejcova et al, 2004;Chiba et al, 2005;Yamada et al, 2008), including transgenic mice expressing familial AD-causing genes (Chiba et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin-like growth factor-binding protein-3 enhances HN rescue activity from A␤ toxicity, whereas HN inhibited insulin-like growth factor-binding protein-3-induced apoptosis in human glioblastoma-A172 (Ikonen et al, 2003). In addition, multiple groups have demonstrated that HN derivatives inhibited memory impairment of AD model animals (Mamiya and Ukai, 2001;Krejcova et al, 2004;Chiba et al, 2005;Yamada et al, 2008), including transgenic mice expressing familial AD-causing genes (Chiba et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…8) This implies that the increase of the ChAT level in cholinergic neurons plays a critical role in cognition enhancement and thus the cholinergic gene locus "VAChT/ChAT" can be a putative target for therapeutic approaches on AD. [9][10][11] Several studies reported that ginsenosides (i.e., Rg1 and Rb1) isolated from ginseng are responsible for ginseng's effects on the central nervous system (CNS) and the peripheral nervous system. 12,13) The objective of this study is to investigate whether five representative ginsenosides (Rb1, Re, Rd, Rg1, and Rg3) have beneficial effects on the cholinergic system and also to examine the possible mechanisms of the most active ginsenosides.…”
mentioning
confidence: 99%
“…Humanin was found to provide neuroprotection against AD-related insults such as Aβ neurotoxicity *75]. The JAK2/STAT3 signaling pathway showed importance in colivelin neuroprotection against AD-related memory loss [78][79][80]. An in vivo study found that colivelin has more potent neuroprotective effects than humanin and ADNF-9 have when tested against Aβ neurotoxicity *73].…”
Section: Adnf-9 Peptide Derived From Activitydependent Neurotrophic Fmentioning
confidence: 99%